Parietaria pollen a new aeroallergen in the city of Valparaiso, Chile (2013)
ABSTRACT: Parietaria pollen has never been considered as a significant cause of pollinosis in Chile; therefore, the sensitization to Parietaria study has never been included in the study of patients with clinical suspicion of pollinosis in this region. The objective of this study was to describe the clinical characteristics of pollinosis caused by Parietaria in the Valparaíso region, related to air concentrations of this kind of pollen. A cross sectional study was performed in the city of Valparaíso. It consisted of two stages: In the first, pollen grains were counted between 1999 and 2001. In the second, a sensitization profile on a patient population diagnosed with ARC (allergic rhinoconjunctivitis) was evaluated. Parietaria judaica (P. judiaca) presented pollination all year long, with aggravation in the spring and summer, and with values reaching 80 grains/m3 (weekly average). These findings determined the transience of the symptoms in this population, which is mainly perennial with seasonal aggravations. A total of 72 atopic subjects were obtained during the whole sample recollection period. P. judaica was the second most frequent cause of sensitization (60 %) after Dermatophagoides in the sample overall. Also, in monosensitized subjects, it was the first cause of pollen sensitization. P. judaica represents the second cause of allergy in Valparaíso and the first cause of pollinosis. These findings suggest the importance of quantifying Parietaria in Valparaíso and near cities, plus investigating the presence of sensitization and symptoms to allergies in a significant proportion of patients in this region.